Balance sheet of pork production and consumption in Nagaland: Implications for strengthening of pork value chain - SINGH, MAHAK; PONGENER, NUNGSHITULA; MOLLIER, R TALIMOA; KADIRVEL, G; BHATTACHARJEE, M; RAJKHOWA, D J; MISHRA, V K (The Indian Journal of Animal Sciences, 2021)
Per capita meat and pork consumption is highest in Nagaland, India. The present study analysed pork production and its consumption in Nagaland, North East India vis-à -vis the pork value chain. In Nagaland, two processes are simultaneously present: a high demand of pork and a continous decline in the pig population. The pig population in Nagaland has decreased by almost 42% since 2007 and almost 20% since 2012. Highest pork production in Nagaland was recorded in 2014â€“2015 with 60.45 thousand metric tonnes and then it declined to 15.77 thousand metric tonnes in 2018â€“2019. Compounded annual growth rate in pig population and pork production saw negative growth rate during last two decades. In consumption basket, pork constitutes almost 50% of total meat consumed. The state is deficit by 51.34% in meat production in 2017-18. The structure of pig value chain is dominated by small holder farms, traditional out dated technology, unorganized input services, lack of infrastructure, and absence of marketing channels. To make the pig value chain competitive, there is urgent need to revamp the pig production technology, strengthen the marketing infrastructure including slaughter houses, and increase in credit flow in the pig sector.